PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN PENYALURAN KREDIT TERHADAP RETURN ON ASSET (ROA) DENGAN NET INTEREST MARGIN (NIM) SEBAGAI VARIABEL INTERVENING (Studi Pada Bank Umum Yang Terdaftar Di BEI Periode Tahun 2012-2016) - Hayati, Nunuk Nur; Lathifah, Ifah; Kusdiasmo, Bambang (STIE AUB Surakarta)
The purpose of this study is to know, test and analyze that the CAR and Distribution of Credit affect the ROA with intervening variable NIM.The scope of research used is Commercial Banks in Indonesia listed on the BEI period 2012-2016. The number of samples in this study amounted to 9 Commercial Banks in Indonesia period 2012-2016. The analysis results show that (1) CAR has positive but not significant effect on NIM. (2) Lending has positive but not significant effect on NIM. (3) CAR has negative but not significant effect on ROA. (4) Lending has a positive and significant impact on ROA. (5) NIM has a positive and significant effect on ROA. (7) Together (simultaneously) the CAR, Credit and NIM have a significant effect on ROA. (8) The indirect effect of CAR on ROA through NIM is higher than through the direct effect of CAR on ROA. (9) Direct influence The channeling of credit to ROA is higher than through the indirect effect of Lending on ROA through NIM. (10) The most dominant influence is direct influence, because the value of direct influence through higher than the indirect effect (intervening). (11) Based on the calculation of the coefficient of determination (R2) of 0.515 this means that the ROA can be explained by the variable CAR, Lending and NIM of 51.5% and the remaining 48.5% described other variables outside the research model for example DPK, LDR and BOPO.Keywords: CAR, LENDING, NIM, ROA.